Medicinal plant activity on Helicobacter pylori related diseases - Wang, Yuan-Chuen (World journal of gastroenterology : WJG, 2014)
More than 50%of the world population is infected with Helicobacter pylori(H.pylori).The bacterium highly links to peptic ulcer diseases and duodenal ulcer,which was classified as a groupⅠcarcinogen in 1994 by the WHO.The pathogenesis of H.pylori is contributed by its virulence factors including urease,flagella,vacuolating cytotoxin A(VacA),cytotoxin-associated gene antigen(Cag A),and others.Of those virulence factors,VacA and CagA play the key roles.Infection with H.pylori vacA-positive strains can lead to vacuolation and apoptosis,whereas infection with cagA-positive strains might result in severe gastric inflammation and gastric cancer.Numerous medicinal plants have been reported for their anti-H.pylori activity,and the relevant active compounds including polyphenols,flavonoids,quinones,coumarins,terpenoids,and alkaloids have been studied.The anti-H.pylori action mechanisms,including inhibition of enzymatic(urease,DNA gyrase,dihydrofolate reductase,N-acetyltransferase,and myeloperoxidase)and adhesive activities,high redox potential,and hydrophilic/hydrophobic natures of compounds,have also been discussed in detail.H.pylori-induced gastric inflammation may progress to superficial gastritis,atrophic gastritis,and finally gastric cancer.Many natural products have anti-H.pylori-induced inflammation activity and the relevant mechanisms include suppression of nuclear factor-κB and mitogen-activated protein kinase pathway activation and inhibition of oxidative stress.Anti-H.pylori induced gastric inflammatory effects of plant products,including quercetin,apigenin,carotenoids-rich algae,tea product,garlic extract,apple peel polyphenol,and finger-root extract,have been documented.In conclusion,many medicinal plant products possess anti-H.pylori activity as well as an anti-H.pylori-induced gastric inflammatory effect.Those plant products have showed great potential as pharmaceutical candidates for H.pylori eradication and H.pylori induced related gastric disease prevention.